Risk analysis of the insertion of biofloc technology in a marine shrimp Litopenaeus vannamei production in a farm in Pernambuco, Brazil: A case study - Soares Rego, Marcelo Augusto; Sabbag, Omar Jorge [UNESP]; Soares, Roberta; Peixoto, Silvio (Elsevier B.V., 2017)
Uncertainties related to the future behavior of projected cash flows cause doubts when choosing investments. Therefore, it is essential to provide information that assist the entrepreneur in decision-making. This study aimed to evaluate the financial indicators and verify the risk of biofloc technology (BFT) and conventional system employed in a shrimp farm in the state of Pernambuco, Brazil. We used the simulation by the Monte Carlo method as a probabilistic analysis of the net present value (NPV) and internal rate of return (IRR). The input variables considered were retail price (US$/kg), feed price (US$/kg), labor value (US$), productivity (kg/ha/year), production cycle period (days) and feed conversion rate (FCR). The cash flows have been designed for 10 years to the discount rates of 10, 13 and 16%. The BFT system showed greater sensitivity to changes in rates, reducing significantly the NPV when interest rates increased. Risk was only observed in the BFT system, with up to 15% of probability when subjected to the discount rate of 16%. Both shrimp production systems represent a significant investment alternative for the rural sector in northeastern Brazil, because even fromthe perspective of risk management, the IRR has 90% probability of ranging from 7.66% to 59.40% for the BFT, and from 67.96% to 201.03% for the conventional systems. Statement of relevance: Brazilian shrimp producers are looking for new technologies to improve their productive performance and to avoid problems related to diseases in conventional pond culture system. They are interested in the biofloc technology (BFT) system, but there are many doubts about financial issues related to this technology. However, few studies evaluate the economic aspects of the different culture systems used in this activity, hampering the decision-making by the producer. Our study verified the viability of the BFT system, as well as the conventional system employed in the northeast Brazilian shrimp farms, but both systems were impacted along the time by productive aspects and changes in the prices of the main inputs used in the production. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Investment analysis; Monte Carlo method; Sensitivity analysis; Biofloc; Shrimp farming